2023
DOI: 10.3390/w15132324
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Concentration and Origin of Polycyclic Aromatic Hydrocarbons in Waters and Bottom Sediments of Lake Baikal and Its Tributaries

Abstract: The aim of this study was the systematization and generalization of data obtained by authors during the last decade and the comparison of these data with those obtained by other authors. Gas chromatography (GC-MS) was used for the determination of PAHs and the positive matrix factorization (PMF) model and principal component analysis (PCA) were used for source apportionment of PAHs. It was found that the total concentration of 16 priority PAHs in surface waters varied from 5 to 200 ng/L, whereas the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Water 2023, 15, x FOR PEER REVIEW 10 of 19 abundant individual PAHs were Chr, Phe, and BaA. At all locations, HMW PAHs (4-6 ring) prevailed, accounting for an average of 65%; similar dominance has been seen in other studies [45,[63][64][65]. The lack of low molecular weight (LMW) PAHs and the prevalence of high molecular weight (HMW) PAHs in the sediment can be related to their octanol-water coefficient (kow) measuring the hydrophobicity of compounds.…”
Section: Compositional Profilesupporting
confidence: 80%
“…Water 2023, 15, x FOR PEER REVIEW 10 of 19 abundant individual PAHs were Chr, Phe, and BaA. At all locations, HMW PAHs (4-6 ring) prevailed, accounting for an average of 65%; similar dominance has been seen in other studies [45,[63][64][65]. The lack of low molecular weight (LMW) PAHs and the prevalence of high molecular weight (HMW) PAHs in the sediment can be related to their octanol-water coefficient (kow) measuring the hydrophobicity of compounds.…”
Section: Compositional Profilesupporting
confidence: 80%
“…Correlation analyses between partitioning coefficients indicated levels of ecosystem contamination, with specific patterns suggesting either sediment or water pollution. The study concluded that the distribution of PAHs is influenced by molecule size and particle distribution, confirming that biomass and fossil fuel combustion are the primary sources [240].…”
Section: Case Studies Of Pah Impact In Specific Water Systemsmentioning
confidence: 69%
“…In a study conducted by Semenov et al [240] on the composition, concentration, and origin of PAHs in the surface waters and bottom sediments of Lake Baikal and its tributaries, the concentrations of PAHs in water and sediments were analyzed using gas chromatography and analytical models for source identification. The findings revealed that PAH concentrations in water ranged from 5 to 200 ng/L and in sediments from 50 to 700 ng/g, with lighter PAHs prevailing in water and heavier ones in sediments due to fractionation in the soil-water system [240]. The main sources of PAHs were identified as biomass and fossil fuel combustion.…”
Section: Case Studies Of Pah Impact In Specific Water Systemsmentioning
confidence: 99%
“…Ulan-Ude is the largest city in the Selenga watershed and home to almost 500,000 people. There are numerous small anthropogenic sources in Ulan-Ude urban agglomeration [75], thus the nitrogen pollution of surface waters from both point and nonpoint sources is quite possible. The impact of N emission from the State District Power Plant (SDPP) located on the Gusinoye lake shore, windward of sub-watershed 9, is also possible.…”
Section: Spatial Distribution Of Ton Exportmentioning
confidence: 99%